Incidence of Rod Shaped Gramnegative Hospital Acquired Bacterial Infection and Antibiotic Resistance: A Retrospective Based Population Study - Jalal Rashid, Kamal (Kurdistan Journal of Applied Research, 2020)
The gram-negative, especially rod shapes vary in the frequencies that they cause the most frequent types of hospital-acquired infection: pneumonia, surgical site infection, urinary tract infection, diabetic infection, burn and bloodstream infection. The presented study determined the microbial spectrum and antimicrobial susceptibility of gram-negative bacteria isolated from various infection sites in hospitalized patients in Sulaimani city. This study included 735 patients who underwent surgical and wound treatment admitted to the hospital. A microbiological standard technique was used for Identification, isolation and antimicrobial susceptibility. The data in this job were scaled into excel sheets and transferred to SPSS (Statistical Package for Social Sciences) version 24.0 software. The significance of associations between variables and predictor done by Chi-square (?2). P-value of <0.05 was regarded significant. Male was the most common cases 52.5%. Patients less than 18 years-old were the most frequently affected 54.3%. Gram negative infection is the most common and most serious complication of burn injuries and it is the majority suspected clinical finding nearly to 60%. The most common bacteria separatedd from wound and sepsis were Pseudomonas aeruginosa 91.91%. Individual pathogens’ incidence differ significantly between location of infection p<0.001. Pseudomonas aeruginosa, only resistant stabled at the lowest rates for Colistine and Imepenim (0.1% and 7.8%) and significant finding was confirmed p<0.001. But highly resistance to Ticarcillin/Clavulanic Acid, Cefepime, Tobramycin, and Gentamicin (85.6%, 80.8%, 79.3%, 79.2%) .In conclusion, these population-based study gram-negative infections predominate in burn wounds. Microbial resistance to the confirmed drugs leads to repeated antimicrobial treatment modifications and long-time of treatments.